Principles of Defense (Rechtmatigheid) In Decision Standing of State Administration - Syofyan Hadi; Tomy Michael (Jurnal Cita Hukum, 2017)
The efforts of Mayor of Medan in creating a clean government in Medan City Government isto promote the rules and policies that have made the central government and implementedby the city government of Medan conditions include (a) the fact Integrity, (b) e-purchasing,(c) e-government, (d) reward (reward) and punishment (punishment), (e) unqualified (WTP)and the Procurement Services Unit (ULP). The role of the Mayor of Medan to prevent andtake action against perpetrators of corruption in the city government of Medan are (a) facingthe principle of transparency in carrying out the functions and duties of office to preventcorrupt practices, (b) make an early warning program of prevention of corruption, (c) andnine steps to eradicate corruption. That support wider community both from the communityorganizations, businesses, and students are needed.